2017
DOI: 10.5625/lar.2017.33.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of commonly used ICR stocks and the characterization of Korl:ICR

Abstract: Mouse is a commonly used animal in life science studies and is classified as outbred if genetically diverse and inbred if genetically homogeneous. Outbred mouse stocks, are used in toxicology, oncology, infection and pharmacology research. The National Institute of Food and Drug Safety Evaluation (NIFDS; former the Korea National Institute of Health) have bred ICR mice for more than 50 years. We investigated to provide users with information and promote accountability to the Korl:ICR. To secure the indigenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 22 publications
1
15
0
3
Order By: Relevance
“…These changes in the parameter values are considered be due to the administration of BoNT/A muscle injection. However, many of the changed clinical pathologic parameter values were found to be within the normal range of reference to the previous studies [25][26][27]. Given that this is the first report of clinical pathology data after intramuscular administration of BoNT/A in ICR mice, our findings are meaningful and justify further experiments.…”
Section: Discussionsupporting
confidence: 74%
“…These changes in the parameter values are considered be due to the administration of BoNT/A muscle injection. However, many of the changed clinical pathologic parameter values were found to be within the normal range of reference to the previous studies [25][26][27]. Given that this is the first report of clinical pathology data after intramuscular administration of BoNT/A in ICR mice, our findings are meaningful and justify further experiments.…”
Section: Discussionsupporting
confidence: 74%
“…Surprisingly, in contrast with the in vitro results, in vivo embryo development was enhanced in 6-month-old mice treated with high frequency of human ASC-CM IV. The mean numbers of implanted fetuses was increased two-fold compared to the control group, which is even higher than the average litter size of young commercial ICR mice [36]. The litter size is an intricate physiological element affected by sequential events including ovulation, fertilization, embryo development, and fetal survival [37].…”
Section: Discussionmentioning
confidence: 99%
“…4 In AD mouse models, melatonin supplementation was found to ameliorate mitochondrial damage and downregulate the expression of key harmful proteins, leading to a significant improvement of cognitive function. [14][15][16] The antioxidative properties of melatonin were reported to prevent the overproduction of damaging free radicals generated from pathological processes in AD and reduce the subsequent neuronal damage that would otherwise have occurred. 17 Several preclinical studies have also indicated that melatonin may play a role in adult neurogenesis (see Tables 1 and 2).…”
Section: Introductionmentioning
confidence: 99%